Beyond epistemic concepts of information: The case of ontological information as philosophy in science - Polak, Paweł (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2022)
This review article discusses the book of Roman Krzanowski, Ontological Information: Information in the Physical World, which is published by World Scientific. Krzanowski’s book makes a very important contribution to the contemporary discussion about the nature of information. The author analyzes the concept of ontological information and its uses in the works of scientists from various disciplines, resulting in an innovative and inspiring analysis that every philosopher involved in the philosophy of information should read.
Keywords: ontological information; philosophy in science; Mark Burgin